Purchases Decision Making Inventory: Measurement Validation in Indonesia - Ishak, Sella; Elgeka, Honey Wahyuni Sugiharto (Jurnal Psikologi, 2023)
The empirical limitations of the Consumer Styles Inventory (CSI) render the formation of dimensions from this measuring tool-less relevant. Scholars have attempted developing Purchase Decision Making Inventory (PDMI) measuring tool to answer cognitive and emotional processes in decision-making. This research examined the validity of the internal structure of the purchasing decision-making inventory (PDMI) measuring device in the Indonesian context. PDMI has two main dimensions, namely emotional and reasoned. The emotional dimension has five sub-dimensions: impulsivity, indebtedness, negative emotions, frustration, and hedonism. The reasoned dimension has three sub-dimensions: saving, reasoning, and information seeking. The main dimensions explain the differences in cognitive and affective processes that occur in consumers when making decisions. The internal structure of PDMI was evaluated using Confirmatory Factor Analysis (CFA) and reliability analysis. The population of this study was Indonesian people aged 18-25 years (M = 20.3 years, SD = 1.55). The sample in this study was 588. The results of the CFA analysis showed that the results fit the data. The model accuracy indices used are the comparative fit index (CFI), Tucker-Lewis index (TLI), and root mean square error of approximation (RMSEA). The CFI value is 0.932, the TLI value is 0.921, and the RMSEA is 0.046. The results of this research are supported by the reliability results of each sub-dimension and the primary dimension of the PDMI measuring instrument, which has a Cronbach's alpha value ≥ 0.6 with a corrected item-total correlation (CITC) ≥ 0.3 which can be concluded that the PDMI measuring device is valid based on internal structure and reliable evidence sources.